A Study on Fingerprint Recognition based on Neural Networks - Joshithasree, P (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 5 No 1 (2021): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Biometrics is the technology of identifying an individual uniquely. Nowadays, fingerprint recognition is mainly used for security applications in various sectors such as government, organisations, libraries, educational institutions, banks etc. In forensic sciences and crime investigations, identification of an individual is necessary. In order to identify the fingerprint pattern of an individual, various methodologies are used. Different extraction methods are used for the extraction and identification of fingerprints like minutiae extraction, filtering methods, graphical methods etc. Fingerprint liveness detection plays a very important role in detecting whether they are fake or not. Convolutional neural network (CNN) has been used to obtain a better liveness detection system as it ensures good accuracy, low error rate, better penetration rate. Fingerprint recognition using neural networks is more effective and its recognition rate is higher when compared with other methods. Neural networks help in performing effective pattern matching to identify fingerprints. Fingerprint recognition has also been utilized in smartphones for protection and privacy. In this study, the concept of neural networks, which works efficiently in biometrics systems, computer vision, image processing, image surveillance, and many other areas, is used to get more accurate results. How to cite this article: Joshithasree P, Preethi PH, Maram B. A Study on Fingerprint Recognition based on Neural Networks. J Adv Res Appl Arti Intel Neural Netw 2021; 5(1): 10-14.